Ethiopia National Food and Nutrition Survey to inform the Ethiopian National Food and Nutrition Strategy: a study protocol - Masresha Tessema; Kaleab Baye; Meseret Zelalem; Arnaud Laillou; Meseret Woldeyohannes; Meron Girma; Alemnesh Petros; Alemayehu Hussen; Aregash Samuel; Danial Abera Dinssa; Feyissa Challa; Stanley Chitekwe; et al. (BMJ Open)
Introduction Ethiopia has made significant progress in reducing malnutrition in the past two decades. Despite such improvements, a substantial segment of the country’s population remains chronically undernourished and suffers from micronutrient deficiencies and from increasing diet-related non-communicable diseases such as diabetes, hypertension and cancer. This survey aims to assess anthropometric status, dietary intake and micronutrient status of Ethiopian children, women and adolescent girls. The study will also assess coverage of direct and indirect nutrition-related interventions and map agricultural soil nutrients. The survey will serve as a baseline for the recently developed Ethiopian Food System Transformation Plan and will inform the implementation of the National Food and Nutrition Strategy.Methods and analysis As a population-based, cross-sectional survey, the study will collect data from the 10 regions and 2 city administrations of Ethiopia. The study population will be women of reproductive age, children aged 0–59 months, school-aged children and adolescent girls. A total of 16 596 households will be surveyed, allowing the generation of national and regional estimates. A two-stage stratified cluster sampling procedure will be used to select households. In the first stage, 639 enumeration areas (EAs) will be selected using probability-proportional-to-size allocation. In the second stage, 26 eligible households will be selected within each EA using systematic random selection. Primary outcomes include coverage of direct and indirect nutrition interventions, infant and young child feeding (IYCF) practices, food insecurity, dietary intakes, mental health, anthropometric status, micronutrient status and soil nutrient status.Ethics and dissemination The protocol was fully reviewed and approved by the Institutional Review Board of the Ethiopian Public Health Institute (protocol no: EPHI-IRB-317–2020). The study is based on voluntary participation and written informed consent is required from study participants. The findings will be disseminated via forums and conferences and will be submitted for publication in peer-reviewed journals.